Mechanism of the Cardioprotective Effects of Docetaxel Pre-administration Against Adriamycin-Induced Cardiotoxicity - Mari Tomonari; Hideto To; Motohiro Nishida; Takashi Mishima; Hitoshi Sasaki; Hitoshi Kurose (Elsevier, 2011)
We revealed that pre-treatment with docetaxel (DOC) 12 h before adriamycin (ADR) administration significantly reduced ADR-induced toxic death compared with the simultaneous dosing schedule that was commonly used in previous studies. We considered that pre-treatment with DOC relieves ADR-induced cardiotoxicity. In this study, we investigated the influence of DOC on the pharmacokinetics and pharmacodynamics of ADR in order to clarify the mechanism by which DOC pre-treatment relieves ADR-induced cardiotoxicity. When ADR and/or DOC was intravenously administered, the DOC pre-treatment (DOC-ADR) group showed significantly less toxic death than the ADR-alone group. We examined hepatopathy, nephropathy, leukopenia, and cardiotoxicity, all of which can cause toxic death. Of these toxicities, ADR-induced cardiotoxicity was significantly relieved in the DOC-ADR group. To elucidate the mechanism by which DOC pre-treatment relieved ADR-induced cardiotoxicity, lipid peroxidation as a proxy for the free radical level and the pharmacokinetics of ADR were measured. There was no difference in the pharmacokinetics of ADR between the ADR and DOC-ADR groups. On the other hand, the DOC-ADR group showed significantly inhibited lipid peroxidation in the heart compared with the ADR group. It was considered that DOC pre-administration inhibited ADR-induced free radicals and decreased cardiotoxicity. Keywords:: docetaxel, adriamycin, cardiotoxicity, free radical, pre-administration